The use of carbon black-TiO2 composite prepared using solid state method as counter electrode and E. conferta as sensitizer for dye-sensitized solar cell (DSSC) applications - Jaafar, Hidayani; Ahmad, Zainal Arifin; Ain, Mohd Fadzil (2018)
In this paper, counter electrodes based on carbon black (CB)-TiO2 composite are proposed as a cost-effective alternative to conventional Pt counter electrodes used in dye-sensitized solar cell (DSSC) applications. CB-TiO2 composite counter electrodes with different weight percentages of CB were prepared using the solid state method and coated onto fluorine-doped tin oxide (FTO) glass using doctor blade method while Eleiodoxa conferta (E. conferta) and Nb-doped TiO2 were used as sensitizer and photoanode, respectively, with electrolyte containing I −/I− 3 redox couple. The experimental results revealed that the CB-TiO2 composite influenced the photovoltaic performance by enhancing the electrocatalytic activity. As the amount of CB increased, the catalytic activity improved due to the increase in surface area which then led to low charge-transfer resistance (RCT) at the electrolyte/CB electrode interface. Due to the use of the modified photoanode together with natural dye sensitizers, the counter electrode based on 15 wt% CB-TiO2 composite was able to produce the highest energy conversion efficiency (2.5%) making it a viable alternative counter electrode.